The Role of Palestinian Universities in Developing the Environmental Behavior of Students - Taffal, Suha Zuhair (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the role of Palestinian universities in the development of environmental behavior among students from their point of view. The study used the descriptive approach and questionnaire as a tool of the study. The main results showed that the degree of the role of Palestinian universities in developing the environmental behavior of students from their point of view is medium at an average of (1.96 out of 3). The role of curriculum domain came first with an average of (2.04), followed by the domain of role of university activities at average of (1.96). The faculty behavior domain came in the third rank with an average of (1.83). based on the in- depth analysis the main conclusion is the universities have no significant role in developing the environmental behavior of their students. The study recommends that the universities have to develop a clear vision and tools to develop and correct the attitudes and behavior of their students and employees toward environmental issues.